Penerapan Teknik Relaksasi Genggam Jari terhadap Penurunan Rasa Nyeri pada Pasien Post Operasi Kraniotomi - Rini Indah Pratiwi; Dian Hudiyawati (Jurnal Ventilator, 2024)
Craniotomy is a neurosurgical procedure for treating diseases or disorders in the head or brain. The craniotomy procedure can cause side effects in the form of pain. Pain is a sensation that arises due to tissue damage, involving a person's physical, emotional and mental reactions. Pain management is a non-pharmacological treatment used in the health world to reduce pain after patients undergo medical procedures. One of the pain management used in this case study is finger grip. This study aims to implement evidence-based practice of the finger grip method to reduce pain. This study uses a descriptive method with a case study approach. This study involved a patient who had undergone craniotomy surgery. Data was collected through interviews and document study. Data processing is carried out using pain scale measurements and monitoring vital signs such as blood pressure, pulse, respiration and temperature. The instruments used were books, pens and pain measurement scale paper. This case study shows that the finger grip technique is effective in reducing pain in patients who are experiencing pain. This is proven by the change in the level of pain when the finger grip management technique was applied for 3 days of application which decreased significantly. The results of the case study show that pain management using the finger grip technique is effective in reducing pain in patients, resulting in a significant reduction in pain scale